2016
DOI: 10.4103/0971-5916.182621
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of epidermal growth factor receptor mutations based on mutation specific immunohistochemistry in non-small cell lung cancer: A preliminary study

Abstract: Background & objectives:Studies have shown that immunohistochemical (IHC) staining using epidermal growth factor receptor (EGFR) mutation specific antibodies, is an easy and cost-effective, screening method compared with molecular techniques. The purpose of present study was to assess the percentage positivity of IHC using EGFR mutation specific antibodies in lung biopsy samples from patients with primary lung adenocarcinoma (ADC).Methods:Two hundred and six biopsies of primary lung ADC were subjected to EGFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
5
16
0
Order By: Relevance
“…The clinical implications of the exon 20 polymorphism need to be further investigated. We found 19.5% EGFR mutations, with EGFR exon 19 deletions and exon 21 mutations being the most prevalent, similar to previously published data [30] . The lower prevalence of EGFR mutations in cytology samples may possibly be attributed to a selection bias; we used only those cases where tumor cellularity was good and where enough diagnostic FNA smears were available in our archives to mitigate medicolegal issues.…”
Section: Discussionsupporting
confidence: 81%
“…The clinical implications of the exon 20 polymorphism need to be further investigated. We found 19.5% EGFR mutations, with EGFR exon 19 deletions and exon 21 mutations being the most prevalent, similar to previously published data [30] . The lower prevalence of EGFR mutations in cytology samples may possibly be attributed to a selection bias; we used only those cases where tumor cellularity was good and where enough diagnostic FNA smears were available in our archives to mitigate medicolegal issues.…”
Section: Discussionsupporting
confidence: 81%
“…Among ADs alone, one previous study showed that cytological features correlate with prognosis, while others found that pattern grading on small biopsies predicts response to chemotherapy . In addition, knowledge of the varied patterns of lung ADs and its recognition will aid in triage of material for molecular analysis …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] In addition, knowledge of the varied patterns of lung ADs and its recognition will aid in triage of material for molecular analysis. [14][15][16] We aimed to predict architectural patterns and analyse nuclear grades of lung ADs on cytology, correlate their concordance with predominant pattern on paired small biopsies, and to assess outcome.…”
mentioning
confidence: 99%
“…In Caucasian populations 10% of patients harbor these mutations, while in East Asian patients the frequency has been reported to be as high as 60% [14,15] . In the Indian population, where there is genetic diversity, a frequency of 23-50% has been reported ( table 2 ) [16][17][18][19][20][21][22][23] . The techniques of mutation testing as well as the type of referrals have varied in these studies.…”
Section: Egfr Mutations: Frequencymentioning
confidence: 99%